2015
DOI: 10.1021/acsami.5b02821
|View full text |Cite
|
Sign up to set email alerts
|

Effective Bone Regeneration Using Thermosensitive Poly(N-Isopropylacrylamide) Grafted Gelatin as Injectable Carrier for Bone Mesenchymal Stem Cells

Abstract: In this study, thermosensitive poly(N-isopropylacrylamide) (PNIPAAm) was grafted onto gelatin via atom transfer radical polymerization (ATRP). The chemical structure of PNIPAAm-grafted gelatin (Gel-PNIPAAm) was confirmed by XPS, ATR-IR, and (1)H NMR characterizations. Gel-PNIPAAm aqueous solution exhibited sol-to-gel transformation at physiological temperature, and was studied as injectable hydrogel for bone defect regeneration in a cranial model. The hydrogel was biocompatible and demonstrated the ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 41 publications
4
75
0
Order By: Relevance
“…PNIPAAM is a synthetic polymer that can be tuned to match the mechanical stiffness of bone once injected at body temperature [157159]. Watson et al demonstrated that decorating PNIPAAM with pendant phosphate groups improved biodegradation and biointegration of the hydrogel with host tissue, as well as support enhanced mineralization, MSC differentiation, and bone formation in a rat cranial defect model [159].…”
Section: Specific Hydrogel Design Choices For Specific Tissue Applmentioning
confidence: 99%
“…PNIPAAM is a synthetic polymer that can be tuned to match the mechanical stiffness of bone once injected at body temperature [157159]. Watson et al demonstrated that decorating PNIPAAM with pendant phosphate groups improved biodegradation and biointegration of the hydrogel with host tissue, as well as support enhanced mineralization, MSC differentiation, and bone formation in a rat cranial defect model [159].…”
Section: Specific Hydrogel Design Choices For Specific Tissue Applmentioning
confidence: 99%
“…79 Poly( N -isopropylacrylamide) (PNIPAAm) and Pluronic ® are typical examples of thermosensitive polymers that have been used for bone cells’ encapsulations. 80,81 …”
Section: Hydrogels: Suitable Micro-environments For Btementioning
confidence: 99%
“…The physical properties of hydrogels can be easily manipulated: thermoresponsive solutions that gelatinize at physiologic temperature can be premixed with either cells or growth factors prior to implantation (26). Alternatively, Han et al have developed a hydrogel formulation consisting of microribbons with variable crosslinking ability, thus allowing for specification of pore size based on desired application.…”
Section: Translational Cell-based Studiesmentioning
confidence: 99%